1970
DOI: 10.4319/lo.1970.15.2.0246
|View full text |Cite
|
Sign up to set email alerts
|

Some Consequences of Brine Pollution in the Bahía Fosforescente, Puerto Rico

Abstract: Brine pollution from a sea-salt works occasionally flows into Bahia Fosforescente causing stagnation, severe anoxia and accumulation of hydrogen sulfide (88 ml/liter) with conscquent toxic effects on local flora and fauna. The bottom brine (salinity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Studies have observed elevated concentrations of sulfide at bottom waters (1.6–3.5 mmol L -1 ) [ 32 ] and in porewaters (0.024–3.2 mmol L -1 ) [ 37 ] throughout the year. High sulfate reduction rates in BB (34.06 mmol L -1 h -1 ) relative to an oceanic station located ca.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have observed elevated concentrations of sulfide at bottom waters (1.6–3.5 mmol L -1 ) [ 32 ] and in porewaters (0.024–3.2 mmol L -1 ) [ 37 ] throughout the year. High sulfate reduction rates in BB (34.06 mmol L -1 h -1 ) relative to an oceanic station located ca.…”
Section: Resultsmentioning
confidence: 99%
“…The BB station (17.972 o N, 67.014 o W) is within The Bioluminescent Bay ( Fig 2 ), 3.2 km east of La Parguera town ( Fig 1 ). The Bioluminescent Bay has a 0.19 km 2 surface area, an average depth of 3.5 m [ 31 ], and a maximum of 4.5 m [ 32 ]. A 25-meter-wide red mangrove ( Rhizophora mangle L.) fringe surrounds the bay and is a significant organic carbon source.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Species richness and density can also decline where extreme salinities are prominent (Bayly, 1972;Vega-Cendejas and Hernández de Santillana, 2004). Increases in the concentration of salts may result in the dehydration of cells, and the inability to hypoosmotically regulate leading to a decrease of turgor pressure and mortality, especially in larvae, eggs and juveniles (Cintron, 1970;Aladin, 1991;Einav et al, 2002;Young and Potter, 2002).…”
Section: Introductionmentioning
confidence: 98%